Activities of the Turkish Maarif Educational Foundation in Confrontation with the Hizmet Movement - Anri R. Chedia (Vestnik RUDN. International Relations, 2023)
Educational programs can be a valuable tool in the cultural diplomacy of modern countries. As a soft power tool, organizations seek to expand their geographic reach by opening educational institutions in different parts of the world in order to spread the influence of their state. In Türkiye, such an organization has long been the Hizmet movement, and in recent years it has been a state-owned the Maarif Foundation . In the study, for the first time in Russian Oriental Studies, an analysis of the activities of the Turkish state Maarif educational foundation in the confrontation with the banned in Türkiye and a number of countries’ Hizmet movements is conducted. Since the declaration of this structure as a terrorist organization on the territory of Türkiye, the Maarif Foundation has been reassigning educational institutions around the world. The most important event in this regard is the coup attempt of July 15, 2016, in which Fethullah Gülen, the ideological mastermind of the movement, was accused. As a result, all schools associated with the Hizmet movement were closed in Türkiye. The relevance of the study is determined by the fact that it considers almost the only case in history of confrontation between two organizations, which are instruments of “soft power” of a country. The purpose of the study is to examine the current issues of the Maarif Foundation’s activities as part of the confrontation with the Hizmet movement. The work includes a qualitative analysis of the official documents of the Turkish state foundation, the laws of the Republic of Türkiye, as well as a discourse analysis of Hizmet’s media products. As a result, it was revealed that despite the rather successful work of the Turkish state educational organization in question, it is not necessary to speak about the complete defeat of Hizmet by the beginning of 2023. By now Maarif state foundation regulates the activity of educational institutions in 49 countries, while according to our calculations the Gülen movement retains a high status in 60 states. It has been revealed that Hizmet’s activities directly or indirectly influence Türkiye’s interstate relations with those countries where Gülen schools operate. It has been established that the demands of the Turkish side to close the institutions of the movement have led to short-lived diplomatic crises between Ankara and some of the host countries. It has been shown that the emergence of Maarif in a particular country does not necessarily lead to the closure of Gülen institutions.